Isolation, molecular detection, and antibiogram study of E. coli isolated from the mastitis milk of crossbred Jersey cows in Puducherry: Isolation and Antibiogram of E. coli from mastitis milk - Sandhiya, Kirouchendraji; R, Sivachandiran; V, Bhanu Rekha; Venkatesh, K.M. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Though mastitis is caused by multiple etiological agents, bacteria are the most common etiological agent. The molecular detection of an organism is less time-consuming and more accurate than conventional methods. Further, to address antimicrobial resistance (AMR), big steps must be taken in animal husbandry practices, which necessitate the development of an AMR database in a particular region or state. Thus, the present study was aimed at conventional as well as molecular detection and the antibiogram study of E. coli from the suspected subclinical (15) and clinical (15) mastitis milk samples collected in Puducherry's Aryankuppam region. All the collected samples were positive for the California Mastitis Test (CMT). Subsequently, nineteen E. coli isolates were isolated, and they were investigated for the presence of bacterial isolates using the PCR technique (uspA gene) as well as biochemical tests. Twelve samples were found positive by PCR (uspA gene). Furthermore, an antibiogram study revealed that penicillin (100%) was highly resistant, followed by nalidixic acid (78%). Notably, the highest susceptibility was observed for ciprofloxacin (92%), followed by gentamicin (85%), and ceftriaxone (71%). The probable isolates obtained must be additionally investigated and warranted by using more mastitis milk samples.
Keywords: Antibiogram; E. coli; Mastitis; Milk; uspA gene